Smoking behaviour and perceived health consequences of environmental tobacco smoke among university athletes in Nigeria (2005)
This study investigated tobacco smoking behaviour and the perceived health consequences of environmental tobacco smoke by university athletes in Nigeria and to determine whether the philosophy of the Nigerian Universities Games Association (NUGAJ, resting on the objective of development of the physical, emotional and mental ideals of students, is still in vogue. The descriptive survey research method was used to collect data, through the use of self-developed and validated questionnaire (of r=0.80 reliability) of randomly selected university athletes that participated in the 19th biennial NUGA Games 2002, held between 11 and 21 December 2002, at the University of Ibadan. Out of the 159 respondents, 61 (38.7%) were smokers - consisting of 51 (83.6%) male and 10 (16.4%) female athletes). The reasons given for smoking included the influence of friends, and for relaxation purposes. The response level on knowledge of items about health consequences of tobacco smoking ranged between 65.4% and. 91.8%, while the level of knowledge of the health consequences of environmental tobacco smoke ranged between 38.5% and 64.8%. With these findings, we suggest educational intervention programmes to empower athletes say ‘No’ to smoking and quit smoking. We also suggested the need for sports councils to call health professionals to put in place tobacco smoking cessation programmes, develop IEC materials on environmental tobacco smoke and peer education programmes targeting university athletes to ensure their wellness